2022
DOI: 10.3390/jcm11133824
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oxybrasion in the Treatment of Acne Vulgaris: A Preliminary Report

Abstract: There are many cosmetic methods to reduce skin eruptions in people with acne vulgaris. As oxybrasion is a safe method of exfoliating dead epidermis, our objective was to investigate its effectiveness in young women with acne vulgaris. The Global Acne Grading System (GAGS) and Derma Unit SSC 3 device (Sebumeter SM 815, Corneometer CM 825) were used to assess acne vulgaris and skin properties. Twenty-four women aged 19–21 years (M = 19.50, SD = 0.66) with diagnosed mild acne vulgaris and a high level of sebum (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Acne, excessive seborrhea, blackheads, whiteheads, and papules were observed. The GAGS scale is used to determine the degree of acne and to also check whether the treatments had a positive effect on the improvement of the skin [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Acne, excessive seborrhea, blackheads, whiteheads, and papules were observed. The GAGS scale is used to determine the degree of acne and to also check whether the treatments had a positive effect on the improvement of the skin [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The author mentions some articles, most of which reported comparative outcomes for at least two groups. 2 , 3 In addition, we note that the treatment outcomes in this study relied primarily on subjective reports from researchers and patients rather than objective indicators. Therefore, if there was no control group in this study, the claim that combination therapy is more effective than other treatments reported for facial postacne erythema is not rigorous.…”
Section: Dear Editormentioning
confidence: 99%
“…2 Acne in adolescence, on a larger scale, reveals different clinical characteristic by the appearance of skin eruptions such as comedones, papules, nodules, pustules, and seborrhea. 3 In China, the prevalence of acne is about 39.2%, 4 compared to 42.2–73.5% in some European countries, with the highest prevalence between the ages of 15–17 years. 5 Additionally, about 33% of people aged 15 to 44 suffer from acne, 6 and the prevalence of acne in adolescents is about 80 to 90%, while it usually subsides by the age of 30.…”
Section: Introductionmentioning
confidence: 99%
“…it mostly occurred in adolescence; (2) it mostly involved areas with developed sebaceous glands, including the face, chest, and back(3) …”
mentioning
confidence: 99%